2018
DOI: 10.4102/aveh.v77i1.426
|View full text |Cite
|
Sign up to set email alerts
|

Eye health knowledge and health-seeking behaviours in Ghana

Abstract: Background: To improve access to comprehensive eye health services within the community, an intervention study that sought to integrate primary eye care (PEC) into existing primary health care (PHC) services, namely Community-based Health Planning and Services (CHPS), was conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In most agrarian African communities, the traditional role of males is associated with breadwinning and any condition that affects a male’s role in providing the necessary financial support is worthy of attention [ 30 ]. This study, on the other hand, could have underrepresented women due to their generally low socioeconomic status which precludes them from accessing health care at the tertiary level [ 31 , 32 ]. This suggests that efforts to stem sex-gender inequalities to access eye care should not be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…In most agrarian African communities, the traditional role of males is associated with breadwinning and any condition that affects a male’s role in providing the necessary financial support is worthy of attention [ 30 ]. This study, on the other hand, could have underrepresented women due to their generally low socioeconomic status which precludes them from accessing health care at the tertiary level [ 31 , 32 ]. This suggests that efforts to stem sex-gender inequalities to access eye care should not be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in the prevalence rate of low vision might have resulted from the increased awareness of eye health amongst parents/guardians of the participants as well as the Ghanaian society at large. 19 Improvement in socioeconomic development and health care could have also contributed to this result. 20 There has also been a general increase in access to eye care services and corrective devices in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging field of genomics offers the potential for greater understanding of the genetic basis for many disorders, including those commonly associated with vision loss and blindness [ 1 ]. The technical and technological aspects of genomic research are unfamiliar to many Africans, as are the nature and impact of common ocular disorders on visual function [ 2 , 3 ]. The current knowledge of genetics and genomics is still very low in Africa despite its potential to reduce the burden of many genetic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these include cost, lack of knowledge, as well as cultural and social barriers [ 8 ]. Ofosu et al [ 3 ] also reported in their study in Ghana that lack of awareness affects health seeking behaviour and eye care service delivery. They reported that although participants in their survey knew that cataract could lead to poor vision, less than a fifth (18.6%) of them could relate cataract with blindness.…”
Section: Introductionmentioning
confidence: 99%